Avoiding inelastic strains in solder joint interconnections of IC devices - Suhir, Ephraim (Boca Raton, FL : CRC Press, 2020)
"The book addresses analytical (mathematical) modeling approaches aimed at understanding the underlying physics and mechanics of the behavior and performance of solder materials and solder joint interconnections of IC devices. The emphasis is on design for reliability, including probabilistic predictions of the solder lifetime. It helps the reader predict and minimize, at the design stage and using analytical modeling concepts and approaches, the stresses and strains in solder joint interconnects of IC devices"--
OCLC-licensed vendor bibliographic record.
Keywords: Interconnects (Integrated circuit technology) -- Protection; Solder and soldering -- Mechanical properties -- Mathematical models; Failure analysis (Engineering); TECHNOLOGY / Electronics / General; TECHNOLOGY / Material Science; Electronic books